The therapeutic potential of Astragalus membranaceus in atopic dermatitis: from traditional applications and modern pharmacological research to regulation of the Gut-Skin Axis - Lu, Chengshuang; Zeng, Yuping; Wang, Guo; Lou, Buqing; Wang, Yifan; Liu, Wancheng; Yan, Zhiming; Fu, Haoyang (Frontiers in Pharmacology, 2025)
Atopic dermatitis (AD) is a difficult-to-treat and recurrent skin condition that often imposes a heavy burden on patients and healthcare systems due to the high costs associated with its treatment and management. Astragalus membranaceus (AM), as a botanical drug, has been shown to alleviate skin diseases through multiple mechanisms. However, its systematic mechanism of action against AD remains unclear. This research summarizes the molecular mechanisms through which AM and its active components (polysaccharides, saponins, flavonoids) mitigate AD. The study proposes, for the first time, that AM may alleviate the onset and progression of AD by inhibiting the translocation of gut-derived inflammatory factors to the skin through the Gut-Skin Axis (GSA). Through comprehensive analysis of network pharmacology, molecular docking, and molecular dynamics simulations, compounds with potentially high activity of AM were preliminarily screened. The potential interaction mechanism between this compound molecule and the target protein in AD treatment was further explored. A total of 89 common targets were identified between AM and AD. Enrichment analysis suggests that signaling pathways such as IL-6, TNF-α, NF-κB, and IL-17 may serve as key regulatory hubs in the progression of AD. At conventional doses, AM exhibits a good safety profile. However, the risk of interactions when combined with traditional AD treatments (such as tacrolimus) warrants attention, necessitating enhanced safety evaluations before clinical application. Overall, AM holds potential as an adjunctive therapy for mitigating side effects and improving symptoms, offering a safer alternative to existing treatments. It contributes to shifting AD treatment strategies from purely symptom control toward addressing both symptoms and underlying causes.